Child standardized patients in pediatric OSCEs: a feasibility study for otoscope examination among undergraduate students in Rwanda - Natalie McCall; Abebe Bekele; Biniam Ewnte; Jonathan Abaho; Olayinka Ibrahim (BMC Medical Education)
Abstract Background Otoscope examinations are a fundamental skill in pediatric care, crucial for diagnosing and managing ear conditions such as otitis media. Traditional training methods for pediatric otoscopic examination often rely on adult standardized patients (SPs) or simulated models, which may not be adequate for pediatric examinations. Objectives This study evaluates the feasibility and effectiveness of use of children as SPs in Objective Structured Clinical Examinations (OSCEs) to assess medical students’ competency in pediatric otoscopy. Methods This descriptive cross-sectional study was conducted at the University of Global Health Equity (UGHE), Rwanda during the final exit examinations. This study included 30 final-year medical students, and six child SPs aged 5–8 years, along with their guardians. Quantitative data were collected using structured questionnaires on students perceived self-efficacy and performance. Qualitative data were obtained through focus group discussions with guardians and child SPs. Results The mean (standard deviation) performance of students at the otoscope examination station was 81.67 (5.7) %, with a significant positive correlation between perceived self-efficacy and actual performance (r = 0.493, p = 0.006). The mean performance at the OSCE station was slightly higher than perceived students’ self-efficacy, (72.5 (6.8) vs. 81.67%. p < 0.001). Students reported high levels of satisfaction with the use of child SPs, with 83.3% recommending their use in pediatric OSCEs. Guardians and child SPs also expressed overall satisfaction, though concerns were noted regarding students’ levels of confidence. and communication skills. Conclusion Incorporating children as SPs in pediatric OSCEs enhances the realism and educational value of otoscope training with positive correlation between perceived self-efficacy and actual performance.